Tissue Culture Technology for Rapid Multiplication of Dendrocalamus giganteus Munro - Arya, Sarita; Rana, P. K.; Sharma, Reetu; Arya, I. D. (Indian Forester, 2006)
Micropropagation of Dendrocalamus giganteus through axillary bud culture is described. Multiple shoots were induced from in-vitro culture of nodal shoot segments containing axillary bud. Nodal segments produced axillary shoots in 2-3 weeks on Murashige and Skoog's (MS) medium supplemented with BAP (10-40 Î¼ M). These shoots were excised from mother explants and subcultured on different concentrations of BAP in MS medium. Highest shoot multiplication rate of 5.44 fold was obtained on 20 Î¼ M BAP medium. On MS medium supplemented with Kn only 3-4 fold shoot multiplication was obtained. The addition of BAP (10 Î¼ M) in the kinetin (10 Î¼ M) supplemented medium enhanced the shoot multiplication rate to 6.35 fold. 16-66 % roots were formed on excised propagules of 3-5 shoots when transferred to MS medium supplemented with 15-25 Î¼ M IBA. The maximum roots per propagule (8.66) and rooting percentage (90 %) was obtained on MS medium supplemented with 25 Î¼ M IBA + 0.05 Î¼ M BAP. These tissue culture raised plants were successfully hardened and acclimatized and transferred to field condition.